Correlation between dietary score and depression in cancer patients: Data from the 2005–2018 National Health and Nutrition Examination Surveys - Xu, Nan; An, Qing (Frontiers in Psychology, 2022)
Aim To investigate the correlation between dietary score and depression in patients with cancer. Methods In this cross-sectional study, data were collected from the National Health and Nutrition Examination Survey (NHANES) 2005–2018, a cross-sectional and nationally representative database, to compare 322 patients with depression to 2,868 with no depression. Mediterranean (MEDS) diet, Dietary Approaches to Stop Hypertension (DASH) diet, and the Healthy Eating Index 2015 (HEI-2015) score were calculated. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Weighted logistic regression models were used to explore the relationship between dietary scores and depression in patients with cancer. Subgroup analysis was performed by sleep disorders, sex, cancer type, number of tumors, and pain relief prescription treatment. Results The final study sample included 3,190 adults, with 56.94% of them being women, representing 2,177 (86.51%) non-Hispanic white adults. After multivariable adjustment, the MEDS score was correlated with a reduced risk of depression in patients with cancer [odds ratio (OR): 0.90, 95% confidence interval (CI): 0.82–0.97, p = 0.010]. Moreover, the MEDS score was correlated with depression in cancer patients with sleep disorders (OR: 0.84, 95% CI: 0.76–0.93, p = 0.001), in female patients with cancer (OR: 0.83, 95% CI: 0.74–0.92, p < 0.001), particularly in female cancer reproductive system patients (OR: 0.69, 95% CI: 0.57–0.82, p < 0.001). MEDS score also showed a decreased risk of depression in patients with 1 cancer (OR: 0.90, 95% CI: 0.82–0.98, p = 0.019). MEDS score (OR: 0.86, 95% CI: 0.86–0.98, p = 0.024) and DASH (OR: 0.91, 95% CI: 0.84–0.98, p = 0.015) score were related to a decreased risk of depression in patients with cancer using pain relief prescription. Conclusion Good diet quality is significantly correlated with decreased risk of depression in patients with cancer. Aligning with the Dietary Guidelines, such as the MEDS diet, may be beneficial to the reduced risk of depression in patients with cancer.